Factors influencing employee perception on performance management system - Fatimah, Mahmud; Nik Anis, Nik Azemi (KnE Social Sciences, 2019)
Without the employee feedback, the developed performance management system (PMS) cannot be assumed as an effective system that able to stimulate their workers to achieve the company’s objectives and targets. This paper aims to identify the implementation of performance management system in the company, to analyze the factors that affect employee perception on PMS, and subsequently to determine the relationship between factors influencing employee perception and PMS. 119 questionnaires were distributed to employees in Company X. The response rate is 43% of the total sample. The finding shows that the respondents strongly agreed on the implemented PMS in the company. Also, employee participation was the highest factor that influencing employee perception of PMS, followed by employee knowledge and skills, and rating techniques. Overall, each of the factors had a significant relationship with the PMS. This study may assist managers in improving their communication with employees on their work performance. Therefore, this will increase the employee understanding of how they have been assessed and feel that the process is fair. Later, this will ensure a positive employee perception of the implemented PMS.